TERAPIA PERIODONTAL DE SOPORTE (TPS) - Sueldo R., Efraín (2000)
The Purpose of this paper is to provide a general overview of the role of supportive periodontal therapy in the treatment of periodontal disease. Reliance on this position paper in patient management will not guarantee a successfull outcome, as periodontal diseases typically involve numerous and complex causas and symptoms. Utilimately, decisions regarding the diagnosis, treatment, and management of disease, as well as subsequent preventive therapy, must be made by the treating practitioner based on the specific circumstances presented by that patient.